Understanding the Relationships between Psychological and Contextual Determinants, Motivation and Achievement Outcomes for Students in Vocational Training or Technical Training Programs - Dubeau, Annie; Plante, Isabelle; Jutras-Dupont, Camille; Samson, Ghislain; Frenay, Mariane (Vocations and Learning, 2021)
In developed countries, obtaining a job qualification is a requirement for securing worthwhile employment. Given, it leads to better social and economic conditions during the entire working life. One relevant avenue to facilitate access to a job qualification, especially for students who have school concerns, is to encourage students to take non-university qualifying training programs like Vocational Training Programs (VT) and Technical training programs (TT). In Quebec (Canada), both of these apprenticeships are carried out in educational establishments; VT being taught in VT centers and TT in colleges (Doray et al. 2008 ; Fédération des Cégeps 2020 ). Currently, relatively few studies have examined the psychological and contextual factors that explain success and persistence through graduation. In response to this lack of data, two studies were conducted with students in VT (study 1) or TT (study 2) training. These studies intended to evaluate a theoretical model to explain students’ school success and persistence in a training program. The proposed model includes two psychological factors (students’ career certainty and future time perspective—FTP), two contextual factors (students’ perceptions of a performance-oriented classroom climate and contextualized instruction) as well as motivation (expectancies of success and subjective task value) and school achievement outcomes (grades and persistence). To evaluate the proposed theoretical model, path analyses were performed on 356 VT students and 503 TT students, enrolled in an apprenticeship in Quebec, Canada. The results of these two studies provide recent data about the factors predicting achievement and persistence according to the type of school/program and about the effects of motivation on achievement indicators in these respective programs. Furthermore, these findings will have important implications to help counselors and educators better adapt VT and TT programs to students’ needs.